INTERACTIVE RELATIONSHIP BETWEEN CONSTITUTIONAL TEXTS AND POLITICAL VARIABLES IN IRAQ: AN ANALYTICAL STUDY IN PUBLIC LAW (2005–2026) - Ridha Raheem Al-Budairy; Alaa Abdul Zahra Baqer; Ameer Majeed Dahdouh Al-Alili; Doaa Ridha Jassim (Veredas do Direito, 2026)
Based on the assumption that the disparity between text and application is not necessarily due to the absence of a suitable legislative text, but rather due to such a dialectic relationship between the legal text and the political reality in the Iraqi state; this research attempts to study the question of how far rules of public law in their theory and their application can quarantine political conflicts and shunt them within an authorized institutional framework so that state functions may run uninterrupted and the recurrent appearance of situations of political deadlock may recede. The study departs from a structural analysis of the Iraqi parliamentary system, focusing in particular on the mechanisms for forming authorities, the contours of the territories that overlap or the nature of political customs of parliamentary behaviour that emerged contemporaneously to codified constitutional texts. The analysis brings the “true” reading of the Constitution as one read through political lenses to the fore and leads to the production of hybrid legal concepts that affix to what seems formally constitutional character the surrounding actual political practice, be it expanding or contracting certain powers according to the balance of powers, irrespective of the letter of the text. We analyse the function of the Federal Supreme Court in interpreting constitutional texts, and the extent to which its decisions have helped consolidate stability or promote existing problems, and how the party system and political agreements affect the effectiveness of the principle of separation of powers. Finally, we examine the problem of the principle of the rule of law in systems with multiple centres of power and weak commitment in institutions. We present a reform vision in the described study, in which we reinforce the principle of the supremacy of law over partisan will, through reaffirming the constitutional text as the highest reference, through activating mechanisms of constitutional oversight, and through developing the legal culture of political actors. We also stress the need to move from a logic of situational compromises to a logic of institutional statehood based on stable rules, hoping to contribute to political stability and the consolidation of good governance.